2018
DOI: 10.1016/j.redox.2018.05.001
|View full text |Cite|
|
Sign up to set email alerts
|

Brain ischemic preconditioning protects against ischemic injury and preserves the blood-brain barrier via oxidative signaling and Nrf2 activation

Abstract: Brain ischemic preconditioning (IPC) with mild ischemic episodes is well known to protect the brain against subsequent ischemic challenges. However, the underlying mechanisms are poorly understood. Here we demonstrate the critical role of the master redox transcription factor, nuclear factor (erythroid-derived 2)-like 2 (Nrf2), in IPC-mediated neuroprotection and blood-brain barrier (BBB) preservation. We report that IPC causes generation of endogenous lipid electrophiles, including 4-hydroxy-2-nonenal (4-HNE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 73 publications
2
46
0
Order By: Relevance
“…Previous in vivo and vitro studies have shown that Nrf‐2 protein expression decreased after oxidative damage . Our findings are consistent with previous researches, but some studies have suggested that Nrf‐2 had transported into the nucleus after ischemia and its expression increased . These discrepancies in mechanism may be due to the use of different animal species and models of ischemic stroke, as well as variations in sampling time points and parts.…”
Section: Discussionsupporting
confidence: 89%
“…Previous in vivo and vitro studies have shown that Nrf‐2 protein expression decreased after oxidative damage . Our findings are consistent with previous researches, but some studies have suggested that Nrf‐2 had transported into the nucleus after ischemia and its expression increased . These discrepancies in mechanism may be due to the use of different animal species and models of ischemic stroke, as well as variations in sampling time points and parts.…”
Section: Discussionsupporting
confidence: 89%
“…However, current research perspectives regard that there is usually an unprotected window with little or no neuroprotection between the first window and the second window (104). Recent research evidence suggests that repeated hypoxic preconditioning can even mediate brain tissue to produce a third protective window that lasts up to 8 weeks of which the underlying mechanism may be caused by epigenetic regulation (106,107).…”
Section: Protection Of Local Ischemic Preconditioningmentioning
confidence: 99%
“…The transmembrane TJs and AJs are mainly composed of claudin-5 and cadherin 5, which are involved in regulating paracellular permeability (201). IPreC can maintain the BBB permeability by directly upregulating the TJs protein claudin 5 and the AJ protein cadherin 5 (109,203) IPreC-induced cytokines, such as TNF-α and interleukin 1β (IL-1β), may affect BBB permeability (106). IPreC can mediate TJs and angiogenic factors levels via activating ERK1/2, implying an essential role of ERK1/2 in paracellular permeability in IPreC (106).…”
Section: Blood-brain Barrier Permeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…As we lack potent treatments to block effects of ischaemia and hypoxia in medicine, mammalian models that help us to better understand tolerance against hypoxia‐anoxia are meaningful. Brain ischaemic preconditioning protects against ischaemic injury via oxidative signalling and Nrf2‐KEAP1 activation . Thus, nutrients and drugs that stimulate Nrf2‐KEAP1 should be tested in conditions with tissue hypoxia .…”
Section: Surviving Hypoxia – Clues Provided In the Animal Kingdommentioning
confidence: 99%